(untitled) (Bulletin KNOB, 2010)
This article deals with the reconstruction of Nederhemert castle, placing it within the wider context of the history, theory and practice of the Netherlands Cultural Heritage Agency. Nederhemert dates back to the fourteenth century and was extended in fourteen building phases to form the castle as it was until the fatal fire in 1945. From that time onwards the burnt-out building was falling into ever further decay. In 2001, prior to the start of the reconstruction, not much more was left of it than a ruin of dilapidated, but from a building-historical point of view very valuable cellars and remnants of walls with medieval brickwork. Two facts were important for the decision to reconstruct this castle and for the way in which this could be done. The building-historical research carried out by J. Kamphuis in 1985 had provided much insight into the building- historical ‘source value’ of the castle. The consultations with experts in the field of castles, building history and preservation of monuments and historic buildings initiated in 1991 by the owner Stichting Vrienden der Geldersche Kastelen was decisive for taking the situation of around 1781 as the starting point for the reconstruction. From 1994-2001 architect W. Kramer was in charge of drawing up the restoration plan. An analysis of the reconstruction plan and the planning and evaluation process made it clear that the dividing line between ‘scientifically sound’ reconstruction and architectonic interpretation is difficult to define both for the owner/commissioner and the official, evaluating Monuments and Historic Buildings Departments. Moreover, a principal discussion on the why and wherefore of reconstruction was avoided. The fact that for this reason the reconstruction of Nederhemert is neither one thing nor the other will be particularly clear when reading the review included in this article of the history, theory and practice of the Netherlands Cultural Heritage Agency in the field of ruins (of castles) and decayed castles. Nederhemert castle resulted in a combination of partial reconstruction and new construction, which was legitimized with arguments given by experts.